Quantum Dots: An Emerging Approach for Cancer Therapy - Devi, Sheetal; Kumar, Manish; Tiwari, Abhishek; Tiwari, Varsha; Kaushik, Deepak; Verma, Ravinder; Bhatt, Shailendra; Sahoo, Biswa Mohan; Bhattacharya, Tanima; Alshehri, Sultan; Ghoneim, Mohammed M.; Babalghith, Ahmad O.; et al. (Frontiers in Materials, 2022)
Nanotechnology is indisputably a scientific technique of therapy and hope for malignant illness. It is a novel technology that offers new approach of diagnosis and management of diverse diseases. Although the discovery of Quantum dots (QD) nano-transporters has virtuous few turns of measures, QD nano-transporters are still at initial stage though have proved more valuable to society. The excertion of QD indicates conversion in natural imaging along with photograph have established incredible suitability in bio-imaging, new drug development, targetted gene deliverance, biosensing, photodynamic treatment as well as diagnosis. The present review aimed to confer the significance of QD in diagnosis as well as in management of cancer. This review aims to impart fundamental insight as well as conception of QD its merits, properties, utilization as well as mode of action. This review highlights of different designing schemes of QD like hydrothermal, drop-casting, ultrasonic, solvothermal, spin-coating, atomic layer testimony, layer by layer, polymethylmethacrylate aided-transfer, electrochemical, ion shaft faltering affidavit. Moreover, we have elaborated on the diverse researches related to cytotoxic examination to reveal that QDs are harmless. Concisely, the present review summarizes the fabrication schemes, current research and utilization of QD in cancer treatment.